Investigating the Prevalence of Gestational Diabetes Mellitus and Its Related Factors in Women Referred To Shahroud Medical- Research Centers - Modoodi , Mozhgan; Nouri , Mahnaz; Ataei , Mina; Amirfakhraei, Azita; Rostami , Khatereh; Jalilvand, Faranak; Ghasemi, Mozhgan (International Journal of Psychosocial Rehabilitation, 2020)
Objective: Considering the importance of gestational diabetes mellitus and different reports on the prevalence and risk factors of this disease, this research was conducted among pregnant mothers referred to Shahrood health centers in 2013 to determine the prevalence and risk factors of gestational diabetes mellitus and glucose tolerance disorder. Method: This is a cross-sectional descriptive-analytical study. The study population was pregnant women who referred to clinics (health centers) in Shahroud for controlling pregnancy. The sample size was estimated at 1000 people. In order to screen for gestational diabetes at 24-28 weeks, all 1000 samples with normal blood glucose at first visit were asked a two-hour oral glucose tolerance test with consuming 75 g glucose (OGTT). Descriptive statistics (frequency, percentage and mean) and inferential statistics (t-test) were used for data analysis by SPSS software. Results: The prevalence of gestational diabetes was 3.8%. Another result was that increasing age increased the risk of gestational diabetes and its subsequent complications. Another point is the relationship between the history of gestational diabetes and type 2 diabetes in relatives and the incidence of gestational diabetes. Conclusion: The results of this study can be considered as an alarm signal for increasing the age of the pregnancy. A pregnant woman with a history of gestational diabetes or type 2 diabetes in her first-degree relatives should know that she has a higher risk of developing gestational diabetes. These can be adjusted by appropriate diet and exercise that can reduce the risk of diabetes during pregnancy and protect the mother and fetus from complications of gestational diabetes.